Refined numerical simulation of a concrete cut-off wall in the thick overburden of dam foundation. (October 2021) - Yu, Xiang; Wang, Yuke; Tulamaiti, Yunusijiang; Zhou, Chenguang; Zhou, Yang; Wang, Gan
Abstract: It is inevitable for dam construction in hydropower exploitation to face a thick overburden foundation with high permeability. The performance of the concrete cut-off wall in an overburden foundation is the key factor to determine dam safety. However, it is difficult to conduct detailed and in-depth study on the wall under complex conditions based on traditional simulation and analysis methods. In this research, the numerical simulation of a concrete cut-off wall in thick overburden are intensively studied. The deformation, stress, and damage distribution of the concrete cut-off wall are analyzed in detail. The importance and necessity of the refined numerical simulation and analysis of a concrete cut-off wall are discussed based on the aspects of scale, grid, analysis content, and method. The results indicate that it is very necessary to conduct a three-dimensional numerical analysis of the cut-off wall. A rough numerical model can be adopted to model the cut-off wall when only deformation is concerned. However, it is necessary to carefully mesh the wall when the stress state is the key research content, and it is more economical and reliable to model the wall with a nonconforming element. Moreover, the plastic damage analysis has revealed that the wall is more liable to tensile damage and the results can be used to establish a direct connection with the anti-seepage performance. In addition, some reinforcement measures have been suggested with a detailed study of the stress generation mechanism and stress direction development process in the concrete cut-off wall. This study can provide a method basis and technical support for the safety design and evaluation of a concrete cut-off wall in the thick overburden of dam foundation.